The Relationship Between Physical Activity And Hypertension Among The Elderly In The Muhammadiyah Regional Leadership (Pdm) Of Sleman - Ujang Candra Irawan; Indriani; Dika Rizki Imania (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Background: Hypertension, commonly referred to as high blood pressure, stands as a leading non-communicable disease responsible for a significant number of global fatalities and health issues. This condition constitutes a primary risk factor for various health complications, including heart disease, stroke, kidney disorders, and dementia. Hypertension frequently develops without noticeable symptoms, earning it the moniker